2014
DOI: 10.1111/jasp.12208
|View full text |Cite
|
Sign up to set email alerts
|

Generational differences in workplace behavior

Abstract: Popular stereotypes suggest that generational differences among workers present challenges for workplace managers. However, existing empirical research provides mixed evidence for generational differences in important values and attitudes. The current study extends generational effects research by examining differences in actual workplace behaviors. Drawing from commonly held generational stereotypes, the authors hypothesized that Baby Boomers would exhibit (Hypothesis 1) fewer job mobility behaviors and (Hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
171
2
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(199 citation statements)
references
References 73 publications
8
171
2
18
Order By: Relevance
“…Thus, we claim that, in European and Euro-Atlantic countries, birth cohorts are not divided significantly with regard to their work values. In this respect, our findings reinforce the results of Clark [57], Kowske et al [17], Jin and Rounds [8], Costanza et al [58], and Becton et al [20]: instead of pointing to any cohort (or generational) differences, we should emphasize the lack of these.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, we claim that, in European and Euro-Atlantic countries, birth cohorts are not divided significantly with regard to their work values. In this respect, our findings reinforce the results of Clark [57], Kowske et al [17], Jin and Rounds [8], Costanza et al [58], and Becton et al [20]: instead of pointing to any cohort (or generational) differences, we should emphasize the lack of these.…”
Section: Discussionsupporting
confidence: 77%
“…• Technologically-savvy (Allen, 2004;Bassett, 2008;Becton et al, 2014;Eisner, 2005;Hershatter & Epstein, 2010;Hills, Ryan, Warren-Forward, & Smith, 2013) • Highly educated (Allen, 2004;Eisner, 2005) • Praise-oriented (Espinoza & Ukleja, 2016;Tulgan, 2009) • Professionally mobile (Barkhuizen, 2014;Bassett, 2008;Becton et al, 2014;Du Plessis et al, 2015;Eisner, 2005;Twenge, 2010) Millennials also have been found to have certain preferences regarding their professional careers:…”
Section: The Millennial Generationmentioning
confidence: 99%
“…Academic literature as well as the popular press have published vast amounts of articles and books on the three generations currently active in today's workforce (Becton et al, 2014;Cennamo & Gardner, 2008;Twenge, 2010;Zopiatis et al, 2012). The majority of generation research has been conducted in Western societies such as the United States, Canada, Europe, Australia, and South Africa (Barkhuizen, 2014;Becton et al, 2014;Cennamo & Gardner, 2008;Lyons et al, 2012).…”
Section: Generation Theorymentioning
confidence: 99%
See 2 more Smart Citations